2020
DOI: 10.1002/adfm.201910556
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Surface Modification Effects on Single‐Walled Carbon Nanotubes for Targeted Sensing and Optical Imaging

Abstract: Optical nanoscale technologies often implement covalent or noncovalent strategies for the modification of nanoparticles, whereby both functionalizations are leveraged for multimodal applications but can affect the intrinsic fluorescence of nanoparticles. Specifically, single-walled carbon nanotubes (SWCNTs) can enable real-time imaging and cellular delivery; however, the introduction of covalent SWCNT sidewall functionalizations often attenuates SWCNT fluorescence. Recent advances in SWCNT covalent functionali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 42 publications
0
58
0
2
Order By: Relevance
“…The optical and electronic properties of single-walled carbon nanotubes (SWCNTs) have long been the focus of nanomaterials research, including the design of biosensors [1][2][3][4][5]. Consequently, modifying SWCNTs with biorecognition elements or biomolecules themselves is a key step in this process [6][7][8][9][10][11], and the functionalization of SWCNTs has been tailored through both covalent and non-covalent approaches [12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The optical and electronic properties of single-walled carbon nanotubes (SWCNTs) have long been the focus of nanomaterials research, including the design of biosensors [1][2][3][4][5]. Consequently, modifying SWCNTs with biorecognition elements or biomolecules themselves is a key step in this process [6][7][8][9][10][11], and the functionalization of SWCNTs has been tailored through both covalent and non-covalent approaches [12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure S10, Supporting Information, we performed the mapping using the excitation laser of 785 nm over a 180 µm × 180 µm area and obtained the RSD of 3.3% for the BPE sample, better than the R6G sample (i.e., 4.4%), validating the prediction of the chemical binding. On the other hand, it has been reported that introducing thiol groups to existing molecules or using thiol molecules as a bridge to connect molecules with sensing chips [ 82–84 ] can improve the sensing performance of non‐thiol‐based molecules. These emerging strategies are promising to expand the impact of the proposed nanogap sensing architectures.…”
Section: Resultsmentioning
confidence: 99%
“…In this work, we placed quantum defects in SWCNTs to perturb the fluorescence response to analyte molecules. Other studies focused more on covalent functionalization chemistry 60 . The data provided mechanistic insights into the sensing mechanism of SWCNT-based fluorescent sensors.…”
Section: Discussionmentioning
confidence: 99%